Nephrotic syndrome in pregnant diabetic women: maternal and perinatal outcomes at a tertiary center - Nogueira, Estela (2023)
Management of pregnant women with diabetic kidney disease and nephrotic range proteinuria or nephrotic syndrome constitute a challenge to clinicians. Maternal and perinatal outcomes, especially in patients with chronic kidney disease, remain poor. The authors describe the multidisciplinary approach and the outcomes of diabetic pregnant patients with nephrotic range proteinuria.